2016
DOI: 10.5543/tkda.2016.03061
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the serum level of CD40 ligand and persistent lone atrial fibrillation

Abstract: The present findings suggest that CD40L levels play a crucial role in the development of lone atrial fibrillation. In addition, results support that regular clinical follow-up of these patients is necessary, due to increased cardiovascular disease risk, determined by elevated CD40L levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Regular clinical follow-up is required in the studied subjects because of the increased risk of CVDs, which is determined by increased CD40L levels. 19 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular clinical follow-up is required in the studied subjects because of the increased risk of CVDs, which is determined by increased CD40L levels. 19 …”
Section: Methodsmentioning
confidence: 99%
“…Regular clinical follow-up is required in the studied subjects because of the increased risk of CVDs, which is determined by increased CD40L levels. 19 Blann et al's study determined that sCD40L levels were marginally elevated in AF patients relative to levels of P-selectin as well as von Willebrand factor. 20 Similarly, Hammwöhner et al's study investigated atrial clot development in persistent AF patients, revealing the consequence of platelet CD40L expression and its relationship with inflammatory markers.…”
Section: Role Of Major Inflammatory Biomarkers In Atrial Fibrillationmentioning
confidence: 99%
“…8 CD40 ligand is considered a part of the tumor necrosis factor family. 8,9 CD40-L has been observed on the surface of many cell lineages including monocytes, macrophages, neutrophils, smooth muscle cells, endothelial cells, and platelets. 10 Recent research has shown that CD40-L expressed on the surface of platelets mediates inflammatory and thrombogenic pathways in the body.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Bozçalı ve ark.nın Türk Kardiyoloji Derneği Arşivi'nin bu sayısında yayınla-nan çalışmasında sadece ısrarcı tek başına AF hastaları incelemeye dahil edilmiş ve CD40L ve CRP düzeyle-ri AF grubunda sağlıklı kontrol grubuna göre anlamlı derecede daha yüksek saptanmıştır. [15] Sadece ısrarcı tek başına AF'li hastaların çalışmaya dahil edilmesi, AF'yi etkileyebilecek sistemik ve yapısal hastalıklar-dan sıyrılmış nispeten saf bir hasta grubunu ele alarak enflamatuvar ve protrombotik süreci etkilemesi olası birçok faktörün ekarte edilmesi bakımından önemlidir. Çalışmada, AF ve kontrol grupları arasındaki, belirteç düzeylerini etkilemesi olası lipit, kan şekeri düzeyleri, kan basıncı, sigara kullanımı açısından da fark saptanmamıştır.…”
unclassified
“…[15] Bu bulgu, her ne kadar nispeten saf bir hasta popülasyonundan elde edilmiş olsa da, karmaşık bir patofizyolojiye sahip bir hastalıkta CD40L düzeylerinin güncel pratikte bir tarama veya tanı testi olarak kullanılması henüz mümkün gö-zükmemektedir.…”
unclassified